Ka Tipu Mai Nga Taiohi Māori: a Study of Taiohi Māori Leaving Care in New Zealand - Leoni, Kerrin (Auckland University of Technology, 2007)
The main purpose of this qualitative study is to identify the problems for young Māori people who have transitioned out of foster care at some stage in their lives. The study has involved interviews with eight Māori care leavers who spoke about their experiences of being in care, conditions when leaving care and what their lives were like afterward. During the interviews they also spoke about their experiences of whānau, hapū and iwi involvement, education, and their own recommendations on how the leaving care process can be improved for future Māori care leavers. A further ten interviews were completed with professionals and community members who at some point had been involved with Māori who had left care. They spoke about their own experiences working with young people leaving care and the work pressures which affect the leaving care process. They also spoke about the involvement of whānau, hapū and iwi during the transition process and their recommendations on improving leaving care practice. There has been extensive research completed regarding the topic overseas in countries such as England, Wales and the USA. However in New Zealand the development of legislative change is only in its initial stages. There have been two studies completed in New Zealand on the topic of leaving care which have resulted in two pilot programmes being developed. These programmes have been developed to test their effectiveness and then assess how the transition towards independence can be improved. The findings raised in this study are specific to the experiences of Māori care leavers. A Māori framework has been used to analyse the findings of the study. These findings have then been transformed into recommendations towards improving policy and practice for Māori and non-Māori leaving care in New Zealand.
Keywords: Taiohi Māori; Leaving care